Strategies for Increasing Performance of Papuan Women Shell Craft Enterprises in Manokwari City: a SWOT Analysis - Imbiri, Soleman; Wambrauw, Ludia Theresia (Igya ser hanjop: Jurnal Pembangunan Berkelanjutan, 2024)
Micro and Small Enterprises (MSEs) are a type of business that plays an important role in increasing a country’s economic growth as it can create jobs, reduce unemployment, create added value in the gross domestic product, and improve people’s lives. However, quite a few Papuan women get involved in MSEs as they have faced various obstacles rather than male. This study investigates strengths, weaknesses, opportunities, and threats of shell craft business carried out by Papuan women in Manokwari city to develop appropriate strategies for increasing their business performance. A mixed-methods research design was employed by conducting a case study, field observation, and in-depth interviews to collect data from eighteen Papuan women enterprises. Then, it is analysed by using SWOT. The finding shows that the most appropriate strategy to be carried out by shell craft enterprises is in III which supports the turnaround strategy. This strategy means that business actors will improve their weaknesses to take advantage of opportunities by (1) equipping themselves with more modern equipment to support production, (2) dividing household tasks to improve business, (3) utilizing social media and websites for online promotion and marketing, (4) running business management, and (5) participating in exhibition events organized by the local government.